Anesthesia Management in a Patient with Unclassified Cardiomyopathy for Transureteral Lithotripsy Surgery - Payman Rezagholi; Arvin Barzanji; Aida Lahorpoor (Advanced Biomedical Research, 2020)
Anesthesia management has always been challenging in cardiac patients, especially patients with cardiomyopathy. There are a variety of cardiomyopathies such as unclassified cardiomyopathy as a complex type that can occur in many forms like left ventricular noncompaction (LVNC) that is an uncommon primary genetic cardiomyopathy typified by noticeable trabeculation of the left ventricular (LV) wall and intertrabecular recesses. We report anesthesia management in a 53-year-old female patient who admitted to the hospital for the transureteral lithotripsy surgery due to dysuria and urolithiasis with a medical history, and echocardiographic examination indicated the diagnosis of hypertension and unclassified cardiomyopathy (LVNC).